2017
DOI: 10.17161/jas.v0i0.5884
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the relationship between the relative age effect and youth development among male house league ice hockey players

Abstract: The current study examined if relative age influences the youth developmental experiences of male house league ice hockey players. Participants completed an on-line survey that solicited their date of birth and responses to the Youth Experience Survey for Sport (YES-S). Our analysis revealed no relative age effect among the house league hockey players. The MANOVA results revealed no significant multivariate differences between quartile of birth and the five YES-S dimensions (p = .493). It is reassuring that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…The primary purpose of this research project was to explore the influence of relative age on positive and negative developmental experiences among post-adolescent competitive female ice hockey players. Our results indicated that competitive female ice hockey players are experiencing the sport in a similar manner, regardless of their quartile of birth, supporting the work of Chittle et al (2017) and Wattie et al (2018). These null results may be positive findings when considering the reports of greater dropout rates among relatively younger athletes (e.g., Canadian population OHF Observed Lemez et al, 2014) and qualitative anecdotes of more negative sporting experiences among the relatively youngest (Edwards & O'Donoghue, 2014).…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…The primary purpose of this research project was to explore the influence of relative age on positive and negative developmental experiences among post-adolescent competitive female ice hockey players. Our results indicated that competitive female ice hockey players are experiencing the sport in a similar manner, regardless of their quartile of birth, supporting the work of Chittle et al (2017) and Wattie et al (2018). These null results may be positive findings when considering the reports of greater dropout rates among relatively younger athletes (e.g., Canadian population OHF Observed Lemez et al, 2014) and qualitative anecdotes of more negative sporting experiences among the relatively youngest (Edwards & O'Donoghue, 2014).…”
Section: Discussionsupporting
confidence: 89%
“…Like Chittle et al (2017), the sample was delimited to include participants who answered a minimum of 80% of the YES-S items and who provided their date of birth to ensure their relative ages could be determined. Four participants were removed from our sample because they did not provide their date of birth, resulting in our final sample comprising 264 participants.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations